Impacts of anthropogenic aerosols on orographic precipitation in Arizona (2023)
ABSTRACT: Water resources are limited in the fast-growing western United States, where increasing drought and warming temperatures are accelerating water losses. In addition, changes in the types and numbers of airborne aerosols can reduce the ability of clouds to efficiently produce precipitation. In this study, we use a cloud-resolving configuration of the Weather Research and Forecasting Model coupled with chemistry to analyze the impacts of anthropogenic aerosols from the urban area of Phoenix on orographic precipitation in the surrounding mountains. Two experiments including aerosol-radiation and aerosol-cloud interactions were performed, one with anthropogenic emissions and the other without anthropogenic emissions. The simulations are performed at 3 km resolution, from March 10–15, 2019. In addition, to assess these interactions for a longer period at a lower computational cost, we employed a four-month dispersion model based on Lagrangian trajectories. The simulations show that aerosols emitted from the Phoenix urban area can reach the windward side of the Mogollon Rim (NE of Phoenix) and interact with supercooled liquid water environments. In this area, the simulation with full emissions results in less frozen precipitation on the windward side of the mountains (∼9%) and a mild increase in frozen precipitation on the lee side (∼8%), consistent with the “spillover” effect. The simulation with the Lagrangian model shows that aerosols emitted from Phoenix constantly reach the mountains near Phoenix, are distributed at heights up to 4-km and enter environments with supercooled liquid water, where aerosol-cloud-precipitation interactions can be strong. This study shows that air pollution from Phoenix can impact winter precipitation in the mountains downwind, affecting the spatial distribution of precipitation in an area with scarce water resources.